Field experiences and lessons learned from applying participatory system dynamics modelling to sustainable water and agri-food systems - Kotir, Julius H.; Jagustovic, Renata; Papachristos, George; Zougmore, Robert B.; Kessler, Aad; Reynolds, Martin; Ouedraogo, Mathieu; Ritsema, Coen J.; Aziz, Ammar Abdul; Johnstone, Ron (Elsevier, 2024)
Achieving the objectives of sustainable development in water and agri-food systems requires the utilisation of decision-support tools in stakeholder-driven processes to construct and simulate various scenarios and evaluate the outcomes of associated policy interventions. While it is common practice to involve stakeholders in participatory modelling processes, their comprehensive documentation and the lessons learned remain scarce. In this paper, we share our experience of engaging stakeholders throughout the entire system dynamics modelling process. We draw on two projects implemented in the Volta River Basin, West Africa, to understand the dynamics of water and agri-food systems under changing environmental and socioeconomic conditions. We outline eight key insights and lessons as practical guides derived from each stage of the participatory modelling process, including the pre-workshop stage, problem definition, model conceptualization, simulation model formulation, model testing and verification, and policy design and evaluation. Our findings demonstrate that stakeholders can actively contribute to all phases of the system dynamics modelling process, including parameter estimation, sensitivity analysis, and numerical simulation experiments. However, we encountered notable challenges, including the time-intensive nature of the process, the struggle to reach a consensus on the modelled problem, and the difficulty of translating the conceptual model into a simulation model using stock and flow diagrams – all of which were addressed through a structured facilitation process. While the projects were anchored in the specific context of West Africa, the key lessons and insights highlighted have broader significance, particularly for researchers employing PSDM in regions characterised by multifaceted human-environmental systems and where stakeholder involvement is crucial for holistic understanding and effective policy interventions. This paper contributes practical guidance for future efforts with participatory modelling, particularly in regions worldwide grappling with sustainable development challenges in water and agri-food systems, and where stakeholder involvement is crucial for holistic understanding of the multiple challenges and for designing effective policy interventions.